2002
DOI: 10.1079/ber2002158
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of global warming on deciduous oak dieback caused by ambrosia fungus Raffaelea sp. carried by ambrosia beetle Platypus quercivorus (Coleoptera: Platypodidae) in Japan

Abstract: Deciduous oak dieback in Japan has been known since the 1930s, but in the last ten years epidemics have intensified and spread to the island's western coastal areas. The symbiotic ambrosia fungus Raffaelea sp. is the causal agent of oak dieback, and is vectored by Platypus quercivorus (Murayama). This is the first example of an ambrosia beetle fungus that kills vigorous trees. Mortality of Quercus crispula was approximately 40% but much lower for associated species of Fagaceae, even though each species had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 14 publications
1
45
0
1
Order By: Relevance
“…In the case of oak dieback in Asia, it was thought that an exotic fungus was introduced and established a relationship with a native ambrosia beetle, Platypus quercivora (Ito and Yamada 1998). Kamata et al (2002), however, rejected this hypothesis and suggested that a more likely explanation is that increased temperatures due to climate change have lead to an expansion of the geographic range of P. quercivora bringing the insect into contact with hosts that are more suitable for brood development and susceptible to its associated ambrosia fungus (Kamata et al 2002). In the case of laurel wilt in the USA, the exotic ambrosia beetle, Xyloborus glabratus, commonly infests healthy native laurel trees without laying eggs.…”
Section: Anthropogenic Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the case of oak dieback in Asia, it was thought that an exotic fungus was introduced and established a relationship with a native ambrosia beetle, Platypus quercivora (Ito and Yamada 1998). Kamata et al (2002), however, rejected this hypothesis and suggested that a more likely explanation is that increased temperatures due to climate change have lead to an expansion of the geographic range of P. quercivora bringing the insect into contact with hosts that are more suitable for brood development and susceptible to its associated ambrosia fungus (Kamata et al 2002). In the case of laurel wilt in the USA, the exotic ambrosia beetle, Xyloborus glabratus, commonly infests healthy native laurel trees without laying eggs.…”
Section: Anthropogenic Effectsmentioning
confidence: 98%
“…Ambrosia beetles, which have seldom been thought of as threats to forests in the past, are now at the forefront of concern in this area. In recent years, there have been increasing numbers of reports of ambrosia beetles attacking apparently healthy trees, and together with their fungal symbionts, causing disease and mortality of large numbers of trees (Wood 1982;Bhagwandin 1993;Kamata et al 2002;Kühnholn et al 2003;Coyle et al 2005). A number of hypotheses have been proposed to explain this increase.…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Fusicolla acetilerea (Tubaki, C. Booth and T. Harada) Gräfenhan & Seifert as fungal associates with X. saxesenii. Fungal species associated with xyleborine ambrosia beetles may cause severe tree diseases such as oak dieback in Asia (Kamata et al 2002) and laurel wilt disease in North America (Mayfield et al 2008;Harrington and Fraedrich 2010). Moreover, xyleborine ambrosia beetles are the perfect candidates for the invasion of new habitats because of their large host plant spectrum and their ability to inbreed.…”
Section: Resultsmentioning
confidence: 99%
“…Its vector, Platypus quercivorus (Platypodinae: Platypodini), transmits the pathogen to members of the Fagaceae, among which there is a considerable range in susceptibility (90,120). Global warming has been proposed as a reason for the development of JOW, as the beetle has extended its geographic range northward into the ranges of previously unencountered host species (80).…”
Section: Greater Understandings Of These Possibilities Are Neededmentioning
confidence: 99%